"The Same Thing That Makes You Live Can Kill You in the End": Exploring the Effects of Growth Rates and Longevity on Cellular Metabolic Rates and Oxidative Stress in Mammals and Birds. (21st August 2018) - Gabriela Jimenez, Ana
Abstract: All aerobic organisms are subjected to metabolic by-products known as reactive species (RS). RS can wreak havoc on macromolecules by structurally altering proteins and inducing mutations in DNA, among other deleterious effects. To combat accumulating damage, organisms have an antioxidant system to sequester RS before they cause cellular damage. The balance between RS production, antioxidant defences, and accumulated cellular damage is termed oxidative stress. Physiological ecologists, gerontologists, and metabolic biochemists have turned their attention to whether oxidative stress is the principal, generalized mechanism that mediates and limits longevity, growth rates, and other life-history trade-offs in animals, as may be the case in mammals and birds. At the crux of this theory lies the regulation and activities of the mitochondria with respect to the organism and its metabolic rate. At the whole-animal level, evolutionary theory suggests that developmental trajectories and growth rates can shape the onset and rate of aging. Mitochondrial function is important for aging since it is the main source of energy in cells, and the main source of RS. Altering oxidative stress levels, either increase in oxidative damage or reduction in antioxidants, has proven to also decrease growth rates, which implies that oxidative stress is a cost of, as well as a constraint on, growth. Yet, in nature, many animals exhibit fast growth rates that lead to higher loads of oxidative stress, which are often linked to shorter lifespans. In this article, I summarize the latest findings on whole-animal life history trade-offs, such as growth rates and longevity, and how these can be affected by mitochondrial cellular metabolism, and oxidative stress.